2012
DOI: 10.1017/s0021932012000284
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Body Composition and Frequency of Overweight and Obesity in Boys Aged 3–18 From Krakow, Poland, Within the Last 30 Years (From 1983 to 2010)

Abstract: The aim of this study was to examine the changes in body composition (fatness and muscle and bone mass) and BMI in three cohorts of boys living in Krakow, Poland, over the last 30 years, and to assess how overweight and obesity frequencies have developed over the period. The anthropological survey was conducted in 2010, and comprised 1863 boys from Krakow aged 3-18 years. The analysis compared the latest measurements of selected skinfold thicknesses, BMI, total body muscle mass and bone mass with the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 59 publications
0
18
2
1
Order By: Relevance
“…In the Kraków children, however, a similar phenomenon was associated with a general decrease in the mid‐upper arm circumference in these age groups. As shown by previous studies, 3‐ to 4‐year‐old children from 2010 were characterized by a lower triceps skinfold thickness than their peers in 1983 (Kowal et al, ; Kryst et al, ). Additionally, the 3‐ to 4‐year‐old boys showed a positive secular trend in mid‐upper arm muscle circumference.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the Kraków children, however, a similar phenomenon was associated with a general decrease in the mid‐upper arm circumference in these age groups. As shown by previous studies, 3‐ to 4‐year‐old children from 2010 were characterized by a lower triceps skinfold thickness than their peers in 1983 (Kowal et al, ; Kryst et al, ). Additionally, the 3‐ to 4‐year‐old boys showed a positive secular trend in mid‐upper arm muscle circumference.…”
Section: Discussionmentioning
confidence: 68%
“…For example, Olds () suggestedthat the positive secular trend with regard to the circumferences of the limbs in recent decades is present due to an increase in body fat. However, in the populations of Kraków, boys have shown an increase in fat and muscle mass as well as a decrease in bone mass (Kowal et al, ). It was different in girls, where the total body fat did not change significantly between 1983 and 2010 (Kowal, Kryst, Woronkowicz & Sobiecki, ).…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, the frequency of overweight and obese children in Poland, between 3 and 18 years, estimated using IOTF standards, shows some regional diversity. Surveys conducted in recent years in Warsaw have revealed that 15.1% of children were overweight and 3.1% were obese (Jarosz and Rychlik, ), in Rzeszów 14.7% and 6.9% respectively (Mazur, ), and 15.9% and 4.9% boys in Kraków (Kowal, ).…”
Section: Introductionmentioning
confidence: 99%
“…The men's attitude towards weight seems to be associated less with the socio-economic status of the family in the transformation context [2]. Research conducted on the population of Kraków over the last 30 years confirms an increase in the prevalence of overweight and obesity in boys and a stabilisation/ slight decrease in the prevalence overweight and obesity in girls [27][28][29]. A question about what the families are really like in which the mother is satisfied with her professional status arises.…”
Section: Discussionmentioning
confidence: 99%